Memilih Pemimpin dalam Islam - Sarkawi Sarkawi; Fadli Ahmad (Idarotuna, 2021)
This article discusses about choosing a leader in Islam. As it is known that the current political dynamics of the nation are often neglected and excluded religion, the rise of demonstrations sometimes demand the leader resignation. Blaming the leader cannot be justified because he is the product and consequence of the election. This research aims to delve how Islam gives guidance to choose a leader. This is a library research in which the data was collected from documents such as journals, books, and manuscripts. They are analyzed in Islamic perspective, and then drawn into conclusion. The research concludes that Islam has taught muslims how to choose a leader. It is quite different from choosing a leader in democracy. In Islam, it is highly recommended and even mandatory to choose a prospective leader who meets the requirements and criteria in Islam, because a voter who determines his voting right is responsible to his religion for his choice. The state of being careless and neglacting in choosing a leader who is not in accordance with Islam will destroy the nation and people. At the end it is all the responsibilities of people, especially muslims to their the Creator.